"An injury to shame": Obscenity and affect in nineteenth‐century German aesthetics. (22nd October 2018) - Weitzman, Erica
Abstract : This article looks at the discourse of obscenity in mid‐ to late nineteenth‐century German legal and aesthetic thought and its implications for both historical and contemporary hermeneutical practices. The article proceeds genealogically from definitions of obscenity in German law (particularly the controversial and widely consequential Lex Heinze of 1893), to the aesthetician Karl Rosenkranz's definition of obscenity as "the intentional injury to shame, " to the programmatic realism of the late nineteenth‐century literary historian and critic Julian Schmidt. Within this genealogy, the obscene emerges as a concept that extends far beyond either legal pragmatics or emotional susceptibility to delineate a particularly suspect play of exposure and concealment, isolation and integration, presence and significance, absorption and theatricality. For the aesthetic thinkers of the late nineteenth century, art and literature must be perpetually on their guard against a certain gratuitous form of sensual spectacle, which not only violates moral conventions, but also threatens a particular idea of the human being and its relationship to the external world in a way that is not merely historical, but continues to be relevant to literary and philosophical debates today.